Fatty acid desaturase genetic variations and dietary omega-3 fatty acid intake associate with arterial stiffness. Issue 2 (16th March 2022) - Bäck, Magnus; Xhaard, Constance; Rouget, Raphael; Thuillier, Quentin; Plunde, Oscar; Larsson, Susanna C.; Girerd, Nicolas; Ferreira, João Pedro; Boivin, Jean-Marc; Bozec, Erwan; Mercklé, Ludovic; Zannad, Faiez; et al.
Abstract: Aims: Long-chain polyunsaturated fatty acids (PUFAs) generate diverse bioactive lipid mediators, which tightly regulate vascular inflammation. The effects of omega-3 PUFA supplementation in cardiovascular prevention however remain controversial. In addition to direct dietary intake, fatty acid desaturases (FADS) determine PUFA levels. Increased arterial stiffness represents an independent predictor of mortality and cardiovascular events. The aim of the present study was to determine the association of PUFA intake, FADS1 genotype, and FADS expression with arterial stiffness. Methods and results: A cross-sectional population-based cohort study of 1464 participants without overt cardiovascular disease was conducted. Dietary intake was assessed using a food frequency questionnaire. Arterial stiffness was assessed by carotid–femoral pulse wave velocity (cfPWV), and the FADS1 locus variant was determined. Blood cell transcriptomics was performed in a subset of 410 individuals. Pulse wave velocity was significantly associated with the FADS1 locus variant. Differential associations between PWV and omega-3 PUFA intake were observed depending on the FADS1 genotype. High omega-3 PUFA intake attenuated the FADS1 genotype-dependent associations. Carriers of the minor FADS1 locus variant exhibited increased expression of FADS2, which is associated with PWV. Conclusion: Taken together, these findings point to FADS1 genotype-dependent associations of omega-3 PUFA intake on subclinical cardiovascular disease. These findings may have implications for identifying responders and non-responders to omega-3 PUFA supplementation and open up for personalized dietary counselling in cardiovascular prevention. Graphical Abstract: Graphical Abstract Interactions between omega-3 intake, FADS genotype, and RNA expression for association with arterial stiffness.